The Effect of Digital Game-Based Learning to Improve Students Learning Outcomes in PAI Class X SMKN 2 Jember - Moh. Khoirur Rosyid Ansori; Nawangsari, Dyah; Fathiyaturrahmah (Universitas Cokroaminoto Palopo, 2025)
This study analyzed the impact of DGBL on the learning outcomes of PAI students in class X SMKN 2 Jember because most of PAI lessons mostly use the lecture method, so learning it needs an interesting innovation to improve student learning outcomes. Using the Quasi-Experiment One-Group Pretest—Post-test Design method with a sample of 35 DKV Class X students, data was collected through pretest and post-test with CP and TP-based instrument. Analysis was conducted using SPSS, including normality, reability, validity, ANOVA, and simple linear regression tests. The results showed a significant increase from the mean score of the pretest (62.8) to the posttest (83.3) and an increase in the percentage of students reaching the KKM from 11% to 91%. DGBL proved to have a significant effect on learning outcomes, with the regression model explaining 93,5% of the observed variation. This study demonstrates that DGBL is effective in improving the motivation and learning outcomes of PAI students, confirming the importance of technology-based learning innovations in religious education.